5‐3: Image Quality Evaluation of Laser Projection Light Field 3D Display. Issue 1 (May 2016) - Hsu, Chun‐Chia; Tu, Shih‐Yu; Lin, Hoang Yan
Abstract : We have set up a wide‐viewing‐zone light field display with low crosstalk by simply using projectors and a diffusion screen, and we also figure out a method to define the perceptual depth for human with subjective experiment.